Artificial Intelligence and Quality of Composition Verdicts in Indonesia: Lessons from New Zealand - Hidayah, Nur Putri; Wicaksono, Galih Wasis; Aditya, Christian Sri Kusuma; Munarko, Yuda (Journal of Human Rights, Culture and Legal System, 2024)
The quality of the decision is not only related to the judge's considerations but also its suitability to the composition of the decision so that the resulting decision is not easily overturned at the level of legal action and increases public confidence in the judicial institution. This research aims to analyze the quality of judges' decisions in Indonesia in terms of the composition of the decision texts that have been made. This research uses normative legal research methods, a statutory approach, and a comparative approach. The study results show that decisions are not based on the structure of decisions determined by the Supreme Court. One of the reasons is the minimal use of AI, even though AI can help judges identify which parts of the decision structure are not yet in the decision prepared by the judge and improve them so that it is hoped that it will produce uniformity and decisions that are certain and not easily overturned. Indonesia needs to learn from New Zealand guidelines for using AI at the court and tribunal level. Judges can apply AI, some related to summarizing information and administration.